2004
DOI: 10.1002/uog.982
|View full text |Cite
|
Sign up to set email alerts
|

Introital ultrasound of the lower genital tract before and after colposuspension: a 4‐year objective follow‐up

Abstract: K E Y W O R D S:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 33 publications
3
51
0
Order By: Relevance
“…The presence and extent of bladder neck funneling ( Fig. 1) were determined as described elsewhere [Schaer et al, 1995a[Schaer et al, , 1996[Schaer et al, , 1999Viereck et al, 2003]. In brief, the depth (d) to which the V-shaped wedge of urine extended along the urethra was determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence and extent of bladder neck funneling ( Fig. 1) were determined as described elsewhere [Schaer et al, 1995a[Schaer et al, , 1996[Schaer et al, , 1999Viereck et al, 2003]. In brief, the depth (d) to which the V-shaped wedge of urine extended along the urethra was determined.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore investigated whether funneling of the bladder neck newly occurring or persisting after the Burch colposuspension is a suitable prognostic indicator of the outcome of surgery. This investigation was performed in the framework of a large retrospective study aimed at assessing the relationship between bladder neck position and surgical outcome including postoperative morbidity [Viereck et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…Since introital and endovaginal ultrasound do not usually visualize the entire symphysis pubis, the lower point of the symphysis has so far been used as a reference point with these techniques (Fig. 3) [7,8,9,10]. However, to obtain reliable results with this method, care must be taken to hold the ultrasound probe in the same position at rest and during the Valsalva maneuver, coughing, and pelvic floor contraction.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…He concluded that the colposuspension procedure reduces angle beta at rest and during straining, restricts linear movement with straining and elevates BN [Viereck et al, 2004a]. The same author determined the BN position by intraoperative introital ultrasound in 90 women during and after colposuspension.…”
Section: Standardizationmentioning
confidence: 94%